Professional competence of the person in the Smart-society - Nina V. Komleva (Открытое образование (Москва))
Now, there are processes of formation of a knowledge society – the Smart-society – are all the new features, which are characterized by obtaining a new effect from the use of information and communication technologies. The development of computers and communications creates the preconditions for moving the place of work out of the office space in the digital home. In these circumstances, more and more importance is given to the individual skills of the person, its ability to absorb a huge amount of diverse information, generate and innovate. Therefore, empowerment process for every professional who wants to be popular, it becomes continuous, becomes a constant need to learn and lifelong learning. In addition, requirements for the employees are changing, and the person must evaluate its relevance to society. This raises the question: how to evaluate the relevance? What is necessary for the Smart-society?What to learn or re-learn? Focus shifts from classical training to personal development. Traditional methods and approaches to learning have stopped covering the needs of the knowledge. Instead of selecting a limited number of the templates, each person is faced with the necessity to configure your own unique personality, to increasingly use informal learning, providing the individual development.The professional competence of the person in the Smart-society is formed in an interactive learning environment, using content from around the world, which is in the public domain. The assessment level of competence, identifying the need for professional development, early learning with the use of technology, provided by the Smart-education, are essential components of the formation process of professional competence of the person in the Smart-society. It is important to provide the compliance of the business metrics of employees to the content of the assessment test at the stage of internal validation for the purpose of timely identification of those competences, it is necessary to increase their level, and certification testing for confirming the level of professional competence of employees, which dictates the ethics of the Economy and Smart-society.This problem causes the need to use the active and relevant content. In order to solve the global task it is necessary to promote development and to use open educational resources. Such active approaches to learning increasingly spread, as the creation of professional communities, the use of cloud computing, mobile communication development.In the context of the professional standards’ implementation, the person should be prepared for such a certification and not pass it by trial and error. The person has to have a possibility to check and to develop the competencies. «Professional communities» can provide such a possibility, in our opinion. Professional community portal – is an effective tool for creating of the high quality and relevant content that can be used for the continuous development of competencies and the employers can submit their claims. Monitoring of competencies, including the monitoring in the centers of the qualification independent assessment should be carried out with the use of adaptive testing algorithms and test tasks continuously updated to meet the changing needs of the Smart-society.